(untitled) (Medico Legal Update, 2020)
Background: Asthma is a common health problem among all age groups. It disturbs all aspects of children’s life and possibly changes to chronic disease that continues for the whole patient’s life. This research focused attention on the parental knowledge and practices during and between asthmatic attacks in order to identify improper activities and improve their future performance toward their children. Objective: This research aims to demonstrate the degree of parental knowledge and behaviours toward their children during and between asthmatic attacks in Mosul City. Method: A case series study was conducted among 312 parents of asthmatic children that attended Al-Khansaa and Ibn-Alatheer teaching hospitals (two major paediatric hospitals in Mosul City)over a period of 6 months. A questionnaire form derived from “the Arabic version of the Chicago Community Asthma Survey Questionnaire” was distributed among the participants to evaluate their demographic characteristics, myths, knowledge, and behaviours. Various rates and proportions are used to explain these variables. Results: This study shows that most parents got information from doctors (62.2%), their best knowledge was about the precipitating factor for asthma as dust and smoke (78%) and the symptoms of asthma as dyspnoea (84.9%), while the least information were about the mechanism of disease where 26.9% did not know the exact mechanism, and the complications of asthma as sudden death (25.3%). On the other hand, the best parental behaviour was the regular use of medications during and between attacks (88.5% and 82.7%) and the lowest ones was performing breathing exercises (around 45%). Conclusion and Recommendation: A relatively adequate knowledge and behaviours were documented in this study; however, further education about the recent guidelines for asthma management should be offered to those parents in order to improve their offspring health and lifestyle.